The contribution of insects to global forest deadwood decomposition - Seibold, Sebastian; Rammer, Werner; Hothorn, Torsten; Seidl, Rupert; Ulyshen, Michael D; Lorz, Janina; Cadotte, Marc W; Lindenmayer, David B; Adhikari, Yagya P; Aragón, Roxana; Bae, Soyeon; Baldrian, Petr; et al. (Nature, 2021)
The amount of carbon stored in deadwood is equivalent to about 8 per cent of the global forest carbon stocks1. The decomposition of deadwood is largely governed by climate2-5 with decomposer groups-such as microorganisms and insects-contributing to variations in the decomposition rates2,6,7. At the global scale, the contribution of insects to the decomposition of deadwood and carbon release remains poorly understood7. Here we present a field experiment of wood decomposition across 55 forest sites and 6 continents. We find that the deadwood decomposition rates increase with temperature, and the strongest temperature effect is found at high precipitation levels. Precipitation affects the decomposition rates negatively at low temperatures and positively at high temperatures. As a net effect-including the direct consumption by insects and indirect effects through interactions with microorganisms-insects accelerate the decomposition in tropical forests (3.9% median mass loss per year). In temperate and boreal forests, we find weak positive and negative effects with a median mass loss of 0.9 per cent and -0.1 per cent per year, respectively. Furthermore, we apply the experimentally derived decomposition function to a global map of deadwood carbon synthesized from empirical and remote-sensing data, obtaining an estimate of 10.9 ± 3.2 petagram of carbon per year released from deadwood globally, with 93 per cent originating from tropical forests. Globally, the net effect of insects may account for 29 per cent of the carbon flux from deadwood, which suggests a functional importance of insects in the decomposition of deadwood and the carbon cycle.
Keywords: Animals; Forests; lesy; koloběh uhlíku; Carbon Sequestration; International Cooperation; stromy; Geographic Mapping; hmyz; geografická kartografie; podnebí; ekosystém; sekvestrace uhlíku; Ecosystem; mezinárodní spolupráce; zvířata; Climate; Trees; Insecta; Carbon Cycle